Comparison of Vascularized Supraclavicular Lymph Node Transfer and Lymphaticovenular Anastomosis for Advanced Stage Lower Extremity Lymphedema. Issue 5 (May 2015) - Akita, Shinsuke; Mitsukawa, Nobuyuki; Kuriyama, Motone; Kubota, Yoshitaka; Hasegawa, Masakazu; Tokumoto, Hideki; Ishigaki, Tatsuya; Togawa, Takashi; Kuyama, Junpei; Satoh, Kaneshige
<x xml:space="preserve">Abstract</x> Background Vascularized lymph node transfer has become a popular surgical option to improve lower extremity lymphedema (LEL), although potential donor sites are limited. The free supraclavicular flap with deep cervical lymph nodes has been recently associated with a minimal risk of secondary lymphedema caused by donor site dissection. However, the effectiveness of this procedure has not yet been evaluated. Methods Vascularized supraclavicular lymph node transfer (VSLNT) was performed for patients with International Society of Lymphology late stage II or more severe LEL. The results were compared with lymphaticovenular anastomosis (LVA) performed for patients with the same stages of severity. To evaluate improvement in lymphatic function, indocyanine green lymphography and lymphoscintigraphy were performed. Results Vascularized supraclavicular lymph node transfer was performed in 13 limbs of 13 patients. The results were compared with 43 limbs of 33 patients who underwent multiple LVA. No severe complications were observed in either group. Improvement in lymphatic function, as measured by the LEL index, was 26.5 ± 4.4 and 21.2 ± 2.0 in the VSLNT and LVA groups, respectively. Lymphatic function was improved in 7 cases in the VSLNT group and 10 cases in the LVA group. Conclusions Vascularized supraclavicular lymph node transfer is an effective technique for the treatment of advanced stage LEL. Lymphaticovenular anastomosis is also effective, but to a lesser degree than VSLNT. However, LVA is less invasive and requires a shorter hospital stay.